Indonesia JURISDICTION OVERVIEW OF Confiscation of Tenant's Property COSTS DUE TO PAYMENT arrears: JURISDICTION OVERVIEW OF Confiscation of Tenant's Property COSTS DUE TO PAYMENT arrears - aritonang, ayu lestari; Ukas (SCIENTIA JOURNAL, 2021)
Thwe fact that often happens in the field is that if the boarding house tenant is latepaying for up to months, then the goods belonging to the boarding house tenant arequickly mortgaged or sold quickly unilaterally to replace losses from late payingboarding fees. From these problems, the authors examine with normative research,namely researching research by examining the aspects of the law and on thedoctrine of experts. From thew resultsw ofw thew studyw thatw thew confiscation owf twheproperty of the boarding tenant cannot be carried out based on the Civil Code, if theboarding house owner has difficulty asking to complete his obligations, he can firstfile a default lawsuit by first giving a subpoena to the boarding tenant as a warningfor negligence in paying rent. For the act of default, the lessor may sue for paymentof rent accompanied by interest win waccordance wwith wArticle 1243 ofw thew Civilw Codew.If the owner wof the boarding house holds the pwroperty owf thew tenant, twhe action owfthwe landlord (the lessor) who holds (confiscates) the goods (the tenant) is againstthe law because it is not carried out based on proper legal procedures. Legalsettlement of confiscation of property belonging to boarding tenants due to arrearsin payments. The act of the owner of the boarding house holding (seizing) yourbelongings as described above is against the law. For this reason, you can apply forcompensation for unlawful acts of the same age aws Artiwcle 1365 owf wthe wCivil Cwode.Solve thwe problem ofw paying thwe rent for this boarding house amicably first. Therenter can discuss again with the owner of the boarding house thwe reasown for thewdelayw orw the reasonw why he is unable to pay the rent two findw thew bestw solutionw forboth partiesw. In addition, the boarding tenant and the boarding house owner canagree together to postpone the rental payment deadline or make it easier to pay rentwith an installment mechanism, which can be used to be written down